Interactions among lactose, spray-dried animal plasma, and soybean meal levels may affect segregated early-weaned pigs - Nessmith, W.B. Jr.; Bergstrom, J.R.; Loughmiller, J.A.; Musser, R.E.; Owen, K.Q.; Smith, J.W. II; Richert, B.T.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Pigs weaned in a segregated early weaning (SEW) environment achieved maximum performance when fed a sequence of diets containing a gradual decrease in spray-dried animal plasma. Furthermore, pigs weaned at approximately 19 days responded positively to 20% soybean meal. Increased levels of lactose enhanced the increases in performance from soybean meal.
Keywords: Swine; Lactose; Spray-dried plasma; Soybean meal; Early-weaned pigs